Strategi Retensi Karyawan dalam Meningkatkan Kinerja Perusahaan pada PT. XYZ - Alya Junieta Dwiyana; Erni Yuningsih (ARZUSIN, 2026)
Employee retention is a strategic issue in human resource management because it directly affects workforce stability and the smooth operation of company activities. PT. XYZ, a company engaged in vegetable cutting and packaging, faces employee retention problems as reflected in its high Labor Turnover (LTO) rate and employee complaints related to career development, reward systems, and employee relations. This study aimed to identify employee retention problems and analyze the company’s efforts to retain employees at PT. XYZ. A qualitative descriptive approach with a field study design was employed, with data collected through observations, interviews with HR personnel and employees, and analysis of supporting data in the form of Labor Turnover (LTO) figures for the 2022–2024 period and a pre-survey of 20 employees as initial respondents. Data were analyzed descriptively to portray the condition of employee retention and the factors influencing it. The findings show that the average Labor Turnover (LTO) rate at PT. XYZ during 2022–2024 was 11.97%, exceeding the normal threshold for employee turnover. The pre-survey and interview results reveal that the main employee retention problems lie in unclear organizational career opportunities, a reward system perceived as not commensurate with work contributions, and less harmonious employee relations due to miscommunication, which collectively reduce employees’ motivation and commitment to remain with the company. The study concludes that employee retention at PT. XYZ is still suboptimal and requires the strengthening of sustainable retention strategies. The practical implications underscore the importance of clear career development pathways, the implementation of a fair reward system, and improved communication and employee relations to enhance retention and reduce employee turnover rates.